Anatomy of a Disappearance - Matar, Hisham (London; Viking; Penguin Group, 2011)
In a voice that is delicately wrought and beautifully tender, Hisham Matar asks, in his extraordinary new novel, when a loved one disappears how does their absence shape the lives of those who are left?
English
Keywords: Libya; PN3311-3503 Literature (General)- Prose. Prose Fiction